Masa Kemunduran Peradaban Islam - Basri, Muhammad; Aprillia, Najwa Dwi; Amelia, Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the 13th to 15th centuries AD, the decline of Islam reached its zenith with the invasions of Genghis Khan and his descendants from Mongolia, devastating various Islamic empires such as Transoxania, Khawarizm, Ghazna, Azarbaijan, and the Seljuks. The culmination of these attacks occurred when Genghis Khan's grandson, Hulagu Khan, conquered Baghdad in 1258 AD, resulting in the city's destruction and the killing of Caliph Al-Musta'sim along with a significant portion of its population. After the destruction of Baghdad in 1258 AD, chaos spread throughout the Islamic world. Egypt became a refuge for some members of the Abbasid family who managed to escape. Egypt emerged as a new center of power, and the Mamluk dynasty rose to prominence as rulers. Meanwhile, attacks continued in other Islamic regions, such as Anatolia and parts of Eastern Europe. In addition to external invasions, internal factors like political fragmentation and dynastic conflicts also contributed to this period of decline.Â